Differentials in technical efficiency among smallholder cassava farmers in Central Madagascar: a Cobb Douglas stochastic frontier production approach - Okoye, B.C.; Abass, A.; Bachwenkizi, B.; Asumugha, G.N.; Alenkhe, B.; Ranaivoson, R.; Randrianarivelo, R.; Rabemanantso, N.; Ralimanana, I. (Informa UK Limited, 2016)
This study employed the Cobb–Douglas stochastic frontier production function to measure the level of technical efficiency among smallholder cassava farmers in Central Madagascar. A multi-stage random sampling technique was used to select 180 cassava farmers in the region and from this sample, input–output data were obtained using the cost route approach. The parameters of the stochastic frontier production function were estimated using the maximum likelihood method. The results of the analysis showed that individual farm-level technical efficiency was about 79%. The study found education, gender and age to be indirectly and significantly related to technical efficiency at a 1% level of probability, and to household size at a 5% level. The coefficient for occupational status was positive and highly significant at a 1% level. The results show that the study’s cassava farmers are not fully technically efficient, showing a mean score of .79%, and suggesting that opportunities still exist for increasing efficiency among the farmers. There is a need, therefore, to ensure that these farmers have access to the appropriate inputs, especially land and capital. The results also call for land reform policies to be introduced, aimed at making more land available, especially to the younger and full-time female farmers.